Amine‐Assisted Delamination of Nb2C MXene for Li‐Ion Energy Storage Devices. (30th April 2015) - Mashtalir, Olha; Lukatskaya, Maria R.; Zhao, Meng‐Qiang; Barsoum, Michel W.; Gogotsi, Yury
<x xml:space="preserve">Abstract</x> 2D Nb2CTx MXene flakes are produced using an amine‐assisted delamination process. Upon mixing with carbon nanotubes and filtration, freestanding, flexible paper is produced. The latter exhibits high capacity and excellent stability when used as the electrode for Li‐ion batteries and capacitors.